2020
DOI: 10.1002/jia2.25609
|View full text |Cite
|
Sign up to set email alerts
|

Retention‐in‐care in the PMTCT cascade: definitions matter! Analyses from the INSPIRE projects in Malawi, Nigeria and Zimbabwe

Abstract: Introduction: Definitions of retention-in-care in Prevention of Mother-to-Child Transmission of HIV (PMTCT) vary substantially between studies and programmes. Some definitions are based on visits missed/made, others on a minimum total number of visits, or attendance at a final clinic visit at a specific time. An agreed definition could contribute to developing evidencebased interventions for improving retention-in-care. In this paper, we estimated retention-in-care rates according to different definitions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Ultimately, the most appropriate measure depends on the intended purpose of the evaluation [ 22 ]. The use cases overlap with the dimensions of engagement with HIV care: different measures are suited to provide the depth of knowledge required to answer different questions, justifying varying burdens of data collection and analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, the most appropriate measure depends on the intended purpose of the evaluation [ 22 ]. The use cases overlap with the dimensions of engagement with HIV care: different measures are suited to provide the depth of knowledge required to answer different questions, justifying varying burdens of data collection and analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Most retention measures were discussed in multiple sources, but multiple thresholds within each measure reduced standardization as different papers used different definitions of “retained” versus “not retained”/“lost to follow‐up” (from 9 weeks [ 88 ] to 180 days [ 49 ] without a visit). Different definitions can result in very different conclusions and the recall period can change the measure of success, worsening the outcomes of more recent time periods [ 5 ]; highlighting the importance of being intentional about how we measure retention for specific purposes [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8,[16][17][18][19][20][21][22][23][24][25] A meta-analysis pooling 6 PMTCT intervention studies in Malawi, Nigeria, and Zimbabwe observed marked variability in retention estimates ranging from 30% to 76% when different definitions were applied within the same data set. 26 This variability makes charting progress and identifying effective interventions challenging across programs.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, the World Health Organization (WHO) published the Prevention of Mother-to-Child Transmission (PMTCT) guidelines which were later updated to include recommendations for lifelong ART for all HIV-positive pregnant and breastfeeding women regardless of their CD4 count or clinical stage (i.e., Option B+) [8]. The updated PMTCT strategy is designed to: achieve the elimination of new paediatric HIV infections; ensure all ART-eligible pregnant women receive treatment; and contribute to ending the AIDS epidemic by 2030 [9][10][11]. Testing and treatment targets have been set by the WHO, which recommend countries to aim for 95% coverage of antenatal care (ANC), 95% HIV testing coverage among pregnant women, and 95% treatment coverage for women diagnosed and living with HIV (known as the WHO 95/95/95 target) [12].…”
Section: Introductionmentioning
confidence: 99%